3D Nanocomposite Architectures from Carbon‐Nanotube‐Threaded Nanocrystals for High‐Performance Electrochemical Energy Storage. (31st October 2013) - Chen, Zheng; Yuan, Yin; Zhou, Huihui; Wang, Xiaolei; Gan, Zhihua; Wang, Fosong; Lu, Yunfeng
<x xml:space="preserve">Abstract</x> Better electrode architecture: spherical assemblies of electrochemically active nanocrystals threaded with carbon nanotubes are made using a simple solvation‐induced‐assembly process. This architecture provides the composites with mechanical robustness, effective ion‐ and electron‐transport pathways, enabling the fabrication of electrodes with high rate, high capacity, and long cycling stability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>